Body Composition Influences Post-Operative Complications and 90-Day and Overall Survival in Pancreatic Surgery Patients - Sónia Velho; Maria Pia Costa Santos; Cátia Cunha; Lisa Agostinho; Rita Cruz; Filipe Costa; Mafalda Garcia; Paulo Oliveira; Rui Maio; Vickie E. Baracos; Marília Cravo (GE: Portuguese Journal of Gastroenterology, 2020)
Introduction: Pancreatic surgery still carries a high morbidity and mortality even in specialized centers. The aim of this study was to evaluate the influence of patients’ body composition on postoperative complications and survival after pancreatic surgery. Methods: This was a retrospective study on patients undergoing pancreatic surgery between March 2012 and December 2017. Demographics, clinical data, and postoperative complications classified according to Clavien-Dindo were recorded. Body composition was assessed using routine diagnostic or staging computed tomography (CT). Multiple Cox proportional hazards models were adjusted. Results: Ninety patients were included, 55% were male, and the mean age was 68 ± 10.9 years. Of these 90, 92% had a total pancreatectomy or pancreaticoduodenectomy, 7% a distal pancreatectomy, and 1% a pancreaticoduodenectomy with multi-visceral resection; 84% had malignant disease. The incidence of major complications was 27.8% and the 90-day mortality was 8.8%. The ratio of visceral fat area/skeletal muscle area (VFA:SMA) was associated with an increased risk of complications (OR 2.24, 95% CI 1.14–4.87, p = 0.03) and 90-day survival (HR 2.13, 95% CI 1.13–4.01, p = 0.019). On simple analysis, shorter overall survival (OS) was observed in patients aged ≥70 years (p = 0.0009), with postoperative complications ≥IIIb (p = 0.01), an increased VFA:SMA (p = 0.007), and decreased muscle radiation attenuation (p = 1.6 × 10–5). In an OS model adjusted for age, disease malignancy, postoperative complications, and body composition parameters, muscle radiation attenuation remained significantly associated with survival (HR 0.94, 95% CI 0.90–0.98, p = 0.0016). A model which included only body composition variables had a discrimination ability (C-statistic 0.76) superior to a model which comprised conventional clinical variables (C-statistic 0.68). Conclusion: Body composition is a major determinant of postoperative complications and survival in pancreatic surgery patients.